2012
DOI: 10.1177/0363546512439027
|View full text |Cite
|
Sign up to set email alerts
|

Leg Dominance Is a Risk Factor for Noncontact Anterior Cruciate Ligament Injuries in Female Recreational Skiers

Abstract: Female skiers showed a 2-fold higher risk of suffering from an ACL rupture on their nondominant leg. Therefore, leg dominance seems to be a risk factor for noncontact ACL injuries in female recreational skiers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
69
0
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(74 citation statements)
references
References 27 publications
2
69
0
3
Order By: Relevance
“…The authors concluded that when injuries were limited to a noncontact injury mechanism (N = 93), females were 68% more likely to injure the ACL in their supporting leg (P < 0.002), whereas males were 74.1% likely to injure their kicking leg (P < 0.002) (Brophy et al, 2010). Ruedl et al (2012) reported that 68% of females injured their non-dominant leg during recreational skiing compared with 48% of males (P = 0.006). Furthermore, Negrete, Schick, and Cooper (2007) and Beynnon et al (2006) also reported a statistically significant tendency for females to injure their non-dominant leg over the dominant leg.…”
Section: Is Limb Dominance Associated With Injury Risk?mentioning
confidence: 99%
See 1 more Smart Citation
“…The authors concluded that when injuries were limited to a noncontact injury mechanism (N = 93), females were 68% more likely to injure the ACL in their supporting leg (P < 0.002), whereas males were 74.1% likely to injure their kicking leg (P < 0.002) (Brophy et al, 2010). Ruedl et al (2012) reported that 68% of females injured their non-dominant leg during recreational skiing compared with 48% of males (P = 0.006). Furthermore, Negrete, Schick, and Cooper (2007) and Beynnon et al (2006) also reported a statistically significant tendency for females to injure their non-dominant leg over the dominant leg.…”
Section: Is Limb Dominance Associated With Injury Risk?mentioning
confidence: 99%
“…Furthermore, lateral preference may also correlate with knee injury risk itself, and therefore its subsequent rehabilitation and recovery (Beynnon et al, 2006;Brophy et al, 2010;Negrete et al, 2007;Ruedl et al, 2012). Clinicians are often asked to make judgements as to when a patient has sufficiently "recovered" from an injury, typically using many common strength-based and dynamic functional outcome measures.…”
Section: Is Limb Dominance Associated With Injury Risk?mentioning
confidence: 99%
“…Only the left leg was analyzed since previous literatures found that female athletes were more likely to tear their left ACL than the right. [29][30][31] Based on these studies, left leg was analyzed to limit data from bilateral subjects with assumed normal growth and risk in both legs.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of anterior cruciate ligament injuries have shown that limb dominance is predictive for the injured side. 29,30 There is currently little information about the use of intracapsular osteotomy in unstable SCFE. Comparison of existing series of intracapsular osteotomy and pinning in situ is fraught with error, as a result of differing methodologies and heterogeneous groups.…”
Section: Timing Of Procedures Following Onset Of Instability Rate Of Amentioning
confidence: 99%